Digital-based public sector innovation: a systematic literature review. - Purnomo, Boyke Rudy; Khabibi, A. Rizal (Innovation: The European Journal of Social Sciences, 2025)
Digital technology has recently played a strategic role in public organisations and presents further discourse by academia. This study aims to determine the current understanding of research in the field of digitally enabled public sector innovation. A systematic literature review was conducted on 87 articles published between 2004 and 2023 in the Scopus database. During this period, the number of articles published on this topic has increased significantly. The findings indicate four main clusters of discussion: public sector innovation and digital transformation, e-government and governance innovation, open government and collaboration, and innovation strategies and platforms. This study identifies various inputs, outputs, and outcomes of digital innovation in public entities. Innovation activities were conducted in four generic phases: planning, adoption, implementation, monitoring, and evaluation. Public organisations employ three basic strategies to facilitate innovation activities: acquisition, usage, and engagement. In addition, diverse digital tools have been employed during the innovation process, ranging from a simple open-source code of social coding platforms and social media to more complicated technologies such as big data, artificial intelligence, and blockchain. This study concludes that several contextual factors affect digitally driven innovation in the public sector. Implications and directions for further research are provided.